Export performance and potential of Singapore - K. Bieda (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1974)
The growth of Singapore as a city started only in the nineteenth century when Sir Stamford Raffles landed there in search of a commercial centre for the (British) East India Company which acquired the whole island in 1824. The island had then only a few traders and fishermen. Shortly, however, it became an important trading and also an administrative centre first for the Straits Settlement, and later also for the Malay States. For its rapid subsequent growth Singapore had literally nothing but: (a) a good port in a good location, on the crossroads of the seas; (b) free port status; (c) a higher degree of security than prevailed in the region (provided by the British power). These meagre assets proved quite adequate to produce an important commercial centre. Until a few years ago Singapore was nothing but an entrepot trade base. Traders of many nations have found it convenient to use Singapore for receiving and handling goods in transit from, and to, all parts of the world, but especially goods moving in the region. This entrepot trade involves buying, e.g., various grades of rubber in small lots from various small producers or traders in the area, putting the lots together, grading them, packing them, and then re-exporting them to any part of the world. For many years, and even now, the local handling of those materials was slight so that the value added per dollar of sales was also slight. The volume of such trade was very high, however, and this gave the island its economic viability. The other element of this entrepot trade consisted in the practice of Singapore merchants buying manufactured goods in large lots in the advanced countries and then breaking-down these lots into small ones convenient for the small business firms in the whole of Southeast Asia, but especially the Malay Peninsula and Indonesia.
Keywords: 330